2015
DOI: 10.1073/pnas.1510342112
|View full text |Cite
|
Sign up to set email alerts
|

Bubble nucleation and migration in a lead–iron hydr(oxide) core–shell nanoparticle

Abstract: Iron hydroxide is found in a wide range of contexts ranging from biominerals to steel corrosion, and it can transform to anhydrous oxide via releasing O 2 gas and H 2 O. However, it is not well understood how gases transport through a crystal lattice. Here, we present in situ observation of the nucleation and migration of gas bubbles in iron (hydr)oxide using transmission electron microscopy. We create Pb-FeOOH model core-shell nanoparticles in a liquid cell. Under electron irradiation, iron hydroxide transfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 54 publications
3
21
0
Order By: Relevance
“…Anatase TiO 2 NPs were immersed in water as 0.1 mol L –1 aqueous suspension and injected into the LETEM through a homemade liquid flow holder (Fig. 1a ) 16 18 . An UV light fiber is introduced in between the pole pieces inside the LETEM, which releases a UV source (characteristic wavelength of 254, 297, 315, 335, 365, 404, and 425 nm) with a flux of 100 mW cm −2 at room temperature (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Anatase TiO 2 NPs were immersed in water as 0.1 mol L –1 aqueous suspension and injected into the LETEM through a homemade liquid flow holder (Fig. 1a ) 16 18 . An UV light fiber is introduced in between the pole pieces inside the LETEM, which releases a UV source (characteristic wavelength of 254, 297, 315, 335, 365, 404, and 425 nm) with a flux of 100 mW cm −2 at room temperature (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Here, we employ a liquid environmental transmission electron microscopy (LETEM) 16 18 to investigate the photocatalytic reactions occurring on the surface of anatase TiO 2 nanoparticles (NPs) immersed in water under ultraviolet (UV) illumination. The photocatalytic reactions found in this research are very different from those observed under vapor conditions in the ETEM 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, during the growth of shell on a core, strain can gradually build up around the interface. It has been reported that the lattice strain can cause phase transformation in the Pt/Au core/shell nanocrystal, and the interfacial strain gradient can facilitate the oxidation of Fe nanoparticles confined in an iron oxide shell . We then examined the strain field at the core–shell interface by the Geometric Phase Analysis (GPA), , based on the high-resolution TEM images of the core–shell particles. The geometric phase obtained here is related to one-dimensional lattice displacement field u x ( r ) along the x direction, where u x ( r ) = −(1/2π) P g ( r ) g , and the g vector (220) of PbS was used for the displacement field determination.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, existing reports on seed-mediated core-shell synthesis do not address the early stages of the formation and growth of the shell, critical in determining the morphology of resultant nanostructures. The in situ fluid cell electron microscopy (EM) is a powerful technique uniquely suitable for the visualization of the formation and growth of NPs in real time and correlating the changes in NP size and shape with the evolution of its crystalline structure (Liao et al, 2012; Kashyap et al, 2014; Alloyeau et al, 2015; Chen Q. et al, 2015; Chen X. et al, 2015; Gamalski et al, 2015; Hellebusch et al, 2015; Hermannsdörfer et al, 2015; Ievlev et al, 2015; Liang et al, 2015a,b; Nagao et al, 2015; Niu et al, 2015; Ross, 2015; Weiner et al, 2016). Recent reports on in situ scanning/transmission electron microscopy (S/TEM) characterization employing gas and liquid cell holder platforms highlighted advances in high-resolution imaging and precise quantification of the particle growth and mobility and pointed to the importance of controlling the electron dose (Williamson et al, 2003; Yuk et al, 2012, 2016; Welch et al, 2013, 2015; Abellan et al, 2014; Lewis et al, 2014; Liao et al, 2014; Woehl et al, 2014; Liu et al, 2015; Ngo and Yang, 2015; Park et al, 2015b,c; Patterson et al, 2015; Pohlmann et al, 2015; Stehle et al, 2015; Woehl and Prozorov, 2015).…”
Section: Introductionmentioning
confidence: 99%